Involving Citizens' Participation is a Guarantee of Targeted Spending of Budget Funds (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article reveals the concept of state audit and the essence of audit with citizen participation. It has been studied how the participation of citizens in effective spending of funds is carried out. Information is provided on what the "audit with participation of citizens" system is, why this system is needed.